2021
DOI: 10.3389/ftox.2021.629451
|View full text |Cite
|
Sign up to set email alerts
|

Methamphetamine Compromises the Adaptive B Cell-Mediated Immunity to Antigenic Challenge in C57BL/6 Mice

Abstract: Methamphetamine (METH) is a substance of abuse that causes dysregulation of the innate and adaptive immunity in users. B cells are involved in the humoral component of the adaptive immunity by producing and secreting antibodies (Abs). METH modifies Ab production, although limited information on the impact of this psychostimulant on antigen (Ag)-specific humoral immune responses is available. Since T cell-dependent and T cell-independent Ags are involved in the activation of B lymphocytes, we explored the role … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…B cells are important for adaptive immunity especially for humoral or antibody‐based responses and antigen presentation. METH alters B cell tissue infiltration and antibody production suggesting a possible detrimental impact on humoral immunity to infection or autoimmunity 36–38 . Thus, we evaluated whether METH compromises B cell and B memory cell populations as well as their DAT expression (Figure 3).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…B cells are important for adaptive immunity especially for humoral or antibody‐based responses and antigen presentation. METH alters B cell tissue infiltration and antibody production suggesting a possible detrimental impact on humoral immunity to infection or autoimmunity 36–38 . Thus, we evaluated whether METH compromises B cell and B memory cell populations as well as their DAT expression (Figure 3).…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Figures 2 and 3, METH did not alter the total number of T and B cells in blood but reduced DAT expression in these immune cells, which is in contrast with studies showing that METH is detrimental to lymphocytes. 5,32,37,51 This could be due to the different model and duration of METH exposure. 52 It is conceivable that METH down-regulates the expression of DAT on the surface of immune cells, thus, compromising the inflammatory or adaptive immune responses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The drug also reduces the production of IL-4 and IFN-γ in splenocytes isolated from METH-treated animals and exposed to ovalbumin ex vivo (Wey et al, 2008). The activation of B lymphocytes, which involves T cell-dependent and T cell-independent antigen, was recently explored in C57BL/6 mice to determine the effects of METH on antibody-mediated immunity to ovalbumin (T cell-dependent) and LPS (T cellindependent) (Mitha et al, 2021). Pulmonary and splenic tissue infiltration by B cells was enhanced by METH seven days post-antigenic challenge.…”
Section: B Cellsmentioning
confidence: 99%
“…In addition, the immunosuppressive effects of METH were shown in animal models, including decreased NK activity and proliferation rate in splenic lymphocytes (Yu et al, 2002 ; Akiyama et al, 2008 ). It has also been reported that METH administration could promote B cell infiltration in the spleen and lung in mice (Mitha et al, 2021 ). However, we observed no significant change in the number of NK and B cells in patients undergoing METH withdrawal.…”
Section: Discussionmentioning
confidence: 90%